Supernatant turbidity and sludge volume in a flocculation process with concomitant use of inorganic and polymer flocculants - Kadooka, Hiroto; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2014)
Flocculation is a typical process which does not progress stoichiometrically. Reproducibility of flocculation with polymer flocculant depends strongly on the amount of additive, the manner of addition and the mixing intensity. It has been found that a dry powder flocculant mixture composed of inorganic flocculant, polymer flocculant and flocculation aid shows high reproducibility of turbidity removal as long as it contains an adequate amount of flocculation aid. The flocculation aid helps the dispersion of the polymer powder into a suspension [1]. Previously, we have reported that the optimum dosage of inorganic flocculant under a given dosage of polymer flocculant decreases as the polymer dosage decreases, and proposed a procedure for determining the optimum composition of a composite dry powder flocculant for turbidity removal [2]. In this study, the procedure is examined by using polymer flocculants of various molecular weights and charge densities. Effects of flocculant dosage on sediment volume and supernatant turbidity are also examined.